Modern views on thyroid disease in individuals after cholecystectomy as a prerequisite for the substantiation and development of a physical rehabilitation program - Golod, Natalia (Journal of Education, Health and Sport, 2018)
Actuality. Gallstone disease (GD) is a disease that affects up to 15% of the adult population. It occurs mainly as a result of the formation of cholesterol gallstones. Sooner or later, 80% of people with gallstones begin to experience gallstone symptoms, which necessarily require surgical removal of the gallbladder - cholecystectomy. Today, it is usually performed laparoscopically. Analyzing the health status of people after cholecystectomy, it was found that often such people have concomitant thyroid disease (TD). TD is a chronic condition that causes physical discomfort. Physical consequences can have a negative and long-term impact on work, hobbies, and psychosocial functions of patients. Objectives of research. To determine the prevalence of thyroid disease in Ukraine. To analyze the impact of thyroid disease in terms of rehabilitation prognosis of patients after cholecystectomy. Identify the main means of physical rehabilitation to improve the quality of life of people with thyroid disease. Results of research. Analyzing the state of health of people after cholecystectomy, it was found that often such people have concomitant thyroid diseases. The most common thyroid pathology in Ukraine today is diffuse and nodular goiter. The number of goiter patients in Ukraine is measured in hundreds of thousands. The incidence of hypothyroidism has increased 6.3 times. Even with subclinical hypothyroidism, the initial stage of TD, symptoms similar to those observed in overt hypothyroidism can occur, leading to a deterioration in quality of life. Conclusions. Endothelial tissues (heart, blood vessels, and capillaries) are most affected in TD. As a result, the function of the cardiovascular system, physical activity, endurance, and muscle strength decrease. Body mass index, heart rate, and blood pressure increase. A lifestyle that helps to maintain body weight, including increased physical activity, reduces the risk of GD. The use of a combination of aerobic and strength exercises in physical rehabilitation programs lasting at least 12 weeks can improve cardiovascular function, increase strength, reduce blood pressure, heart rate, and body mass index.